The history and future of digital health in the field of behavioral medicine. - Arigo, Danielle; Jake-Schoffman, Danielle E.; Wolin, Kathleen; Beckjord, Ellen; Hekler, Eric B.; Pagoto, Sherry L. (Journal of Behavioral Medicine, 2019)
Since its earliest days, the field of behavioral medicine has leveraged technology to increase the reach and effectiveness of its interventions. Here, we highlight key areas of opportunity and recommend next steps to further advance intervention development, evaluation, and commercialization with a focus on three technologies: mobile applications (apps), social media, and wearable devices. Ultimately, we argue that future of digital health behavioral science research lies in finding ways to advance more robust academic-industry partnerships. These include academics consciously working towards preparing and training the work force of the twenty first century for digital health, actively working towards advancing methods that can balance the needs for efficiency in industry with the desire for rigor and reproducibility in academia, and the need to advance common practices and procedures that support more ethical practices for promoting healthy behavior.